Policy Implementation Of Family Welfare Empowerment Program (Pkk) In Improving Women's Empowerment In Sukamantri Village, Cisaat District, Sukabumi Regency - Santi Legianti Sutandi (IHSA Institute, 2022)
Building a development program in the community, in its implementation it is very important to pay attention to who the participants will receive empowerment. This is intended so that the reception of information becomes balanced and equal between participants who have different ways of thinking as a result of different life experiences. This is done so that the community development programs that are implemented can be implemented properly. DIn this case, the focus of the research focuses on the issue of implementing the Family Welfare Empowerment Program (PKK) policy in Sukamantri Village which is related to women's empowerment. In qualitative research, the problem brought by the researcher is still dim, even dark, complex and dynamic.” Therefore, problems in qualitative research are still temporary, tentative and will develop or change after the researcher is in the field.